The social networks support to the feminine transsexuals - Soares, Milene; Feijó, Marianne Ramos; Valério, Nelson Iguimar; Siquieri, Carmem Lúcia dos Santos Maia; Pinto, Maria Jaqueline Coelho (Paidéia (Ribeirão Preto), 2011)
This study aimed at understanding the current ratio of feminines transsexuals with their social networks. The participants were five patients undergoing reassignment surgery in a public hospital in the state of Sao Paulo, B razil. They responded to the semi-structured interview questions for the construction of Genograms and Network Maps. The data were understood in a qualitative way from the new paradigm systemic-cybernetic theory. Interviewees reported situations where they felt supported, even before the decision to operate, but also described situations in which they felt humiliation and exclusion by the fact express and live their sexuality differently from most people. The study showed that still prevails heteronormative position, supporting acts of prejudice and discrimination directed at women transsexuals.